CUSUM chart method for continuous monitoring of antifouling treatment of tubular heat exchangers in open-loop cooling seawater systems. Issue 1 (2nd January 2020) - Boullosa-Falces, David; García, Sergio; Sanz, David; Trueba, Alfredo; Gomez-Solaetxe, Miguel Angel
Abstract: A CUSUM chart method is presented as an alternative tool for continuous monitoring of an electromagnetic field-based (EMF) antifouling (AF) treatment of a heat exchanger cooled by seawater. During an initial experimental phase, biofilm growth was allowed in a heat exchanger formed of four tubes until sufficient growth had been established. In two of the tubes, continuous EMF treatment was then applied. The heat transfer resistance and heat duty (heat transfer per unit time) results showed that biofilm adhesion was reduced by the EMF treatment. EMF treatments resulted in a 35% improvement in the heat transfer resistance values. The proposed CUSUM chart method showed that the EMF treatment increased the useful life of the heat exchanger by ∼20 days. Thus, CUSUM charts proved to be an efficient tool for continuous monitoring of an AF treatment using data collected online and can also be used to reduce operation and maintenance costs.